Molecular mimicry in the pathogenesis of autoimmune rheumatic diseases - Michaela Fehringer; Thomas Vogl (Journal of Translational Autoimmunity)
Autoimmune rheumatic diseases (ARDs) are a heterogeneous group of conditions characterized by excessive and misdirected immune responses against the body's own musculoskeletal tissues. Their exact aetiology remains unclear, with genetic, demographic, behavioural and environmental factors implicated in disease onset. One prominent hypothesis for the initial breach of immune tolerance (leading to autoimmunity) is molecular mimicry, which describes structural or sequence similarities between human and microbial proteins (mimotopes). This similarity can lead to cross-reactive antibodies and T-cell receptors, resulting in an immune response against autoantigens. Both commensal microbes in the human microbiome and pathogens can trigger molecular mimicry, thereby potentially contributing to the onset of ARDs.In this review, we focus on the role of molecular mimicry in the onset of rheumatoid arthritis and systemic lupus erythematosus. Moreover, implications of molecular mimicry are also briefly discussed for ankylosing spondylitis, systemic sclerosis and myositis.